Tuning the Structural, Microstructural and Optical Properties of ZnO with Different Concentration of Cr Doping - Bikram Keshari Das; Tanushree Das; Dipteerekha Das (Research Aspects in Chemical and Materials Sciences Vol. 6, 2023)
A systematic study on the structural, microstructural and optical properties of Cr doped ZnO nanoceramics with different milling time and temperature has been reported. The weight percent of Cr in ZnO varies from 1 to 4% and the milling time varied from 2h to 10h. X-ray diffraction (XRD) data reveals that up to 3% of Cr can be doped in to ZnO after 10 hour of milling showing single phase polycrystalline Cr-doped ZnO, but for x = 0.04 few peaks related to Cr2O3 was noticed. But after calcination at 900 \(^°\)C no additional peak related to Cr2O3 was observed for x = 0.04 sample forming single phase. So up to x = 0.04 Cr is below the solubility limit of Cr in ZnO by ball milling. The data is well matched with rietveld refinement of XRD pattern. Particle growth was observed from FESEM micrograph after calcination and sintering. The band gap of 2% of Cr doped ZnO varies from 3.18eV to 3.06eV with milling from 2hr to 10hr again with increasing Cr concentration from x = 0 to x = 0.04 the variation of band gap was from 3.22eV to 3.235eV. Cr doped ZnO shows blue shift with doping concentration and sintering.